2016
DOI: 10.1007/s12281-016-0268-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Fungal Infections in Cystic Fibrosis

Abstract: For a long time, the microbiology of cystic fibrosis has been focussed on Pseudomonas aeruginosa and associated Gram-negative pathogens. An increasing body of evidence has been compiled demonstrating an important role for moulds and yeasts within this complex patient group. Whether or not fungi are active participants, spectators or transient passersby remain to be elucidated. However, functionally, they do appear to play a contributory role in pathogenesis, albeit we do not know if this is a direct or indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 87 publications
(113 reference statements)
1
46
0
1
Order By: Relevance
“…Cystic fibrosis (CF) is the most common monogenetic autosomal recessive disease in Northern Europe. The disease is caused by mutations in a cystic fibrosis transmembrane conductance regulator (CFTR) gene whose product is a chloride channel (Williams et al [ 1 ]). CFTR mutations result in reduced excretion of chloride ions in the apical membrane of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystic fibrosis (CF) is the most common monogenetic autosomal recessive disease in Northern Europe. The disease is caused by mutations in a cystic fibrosis transmembrane conductance regulator (CFTR) gene whose product is a chloride channel (Williams et al [ 1 ]). CFTR mutations result in reduced excretion of chloride ions in the apical membrane of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The colonization of the lower respiratory tract with microorganisms progresses with the duration of cystic fibrosis. In the early phases, the most common bacteria are Staphylococcus aureus and Haemophilus influenzae , whereas a wide range of bacteria, mainly Pseudomonas aeruginosa , Burkholderia cepacia complex, and other Gram-negative bacteria as well as fungal species, are isolated in the later stages of the disease [ 1 ]. There are several studies analyzing the prevalence of the pathogenic bacteria and fungi in patients with CF (for recent reviews, see [ 3 5 ]).…”
Section: Introductionmentioning
confidence: 99%
“…and Aspergillus spp.) [18] in the airways of people with CF, although their involvement in respiratory disease remains controversial and largely understudied [10,19,20]. Metagenomic studies have also revealed an impact of respiratory viral infections in CF airway damage [21][22][23], as well as the presence of bacterial viruses (phages) in CF airways [24,25].…”
mentioning
confidence: 99%
“…However, as the disease progresses, the lung microbiome of patients with CF is dominated by the bacterium Pseudomonas aeruginosa [33]. Some recent studies have reported that co-colonisation of the airways by C. albicans or A. fumigatus with P. aeruginosa lead to more exacerbations and decreased lung function [34,35]. Other fungal species frequently detected in the airways from patients with CF include Penicillium species, nonfumigatus Aspergillus species, Scedosporium, Exophiala Fig.…”
Section: The Mycobiome and Chronic Lung Diseasesmentioning
confidence: 99%